2019
DOI: 10.14740/jem611
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Anti-Malarial Drug, Hydroxychloroquine, on Glucose and Lipid Metabolism in Japanese Population

Abstract: Background: Hydroxychloroquine (HCQ) is a synthetic anti-malarial drug and has been used for the treatment of rheumatic diseases. Recently, HCQ has been reported to improve lipid and glucose metabolism in patients with rheumatic diseases. However, effects of HCQ on lipid and glucose metabolism in Japanese remain unknown. Methods: We picked up patients who had been prescribed HCQ for 1 month or longer between September 2015 and August 2018. We compared the data at baseline and at 1-11 months after the start of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
4
0
1
Order By: Relevance
“…Interestingly, HCQ generally has protective actions against dyslipidemia (high blood lipid levels). This can lead to a reduction in cardiovascular diseases, systemic lupus erythematosus and rheumatic diseases (Cairoli et al, 2012;Masui et al, 2019;Morris et al, 2011). However, the consequences of the synergistic negative effect of AZT and HCQ on triglyceride levels still need to be further studied.…”
Section: Biochemical Effectsmentioning
confidence: 99%
“…Interestingly, HCQ generally has protective actions against dyslipidemia (high blood lipid levels). This can lead to a reduction in cardiovascular diseases, systemic lupus erythematosus and rheumatic diseases (Cairoli et al, 2012;Masui et al, 2019;Morris et al, 2011). However, the consequences of the synergistic negative effect of AZT and HCQ on triglyceride levels still need to be further studied.…”
Section: Biochemical Effectsmentioning
confidence: 99%
“…Lower HOMA-IR was also seen in rheumatoid arthritis patients receiving HCQ 46 . In Japanese population, it was also found that patients with SLE or rheumatoid arthritis (n=26; aged 46 ± 16 years) prescribed with HCQ with mean daily dose of 284.6 ± 67.5 mg had lower HbA1c after five and six months of HCQ 47 . On the contrary, distinct findings were obtained from a randomised, blinded crossover trial.…”
Section: The Anti-hyperglycaemic Action Of Chloroquinementioning
confidence: 93%
“…However, the most likely interaction between methotrexate and CQ is the reduction of methotrexate bioavailability when co-administered with CQ 63 . In a study recruiting SLE patients (n=22) and rheumatoid arthritis (n=4) patients prescribing HCQ for more than a month, the lipid profile of these patients improved significantly visualised by the lowering of TG, LDL-C and non-HDL-C 47 . In addition, significant decreases in TC, atherogenic index and increase in HDL-C were also noted in female patients with Sjögren's syndrome (n=71; aged 64 ± 11 years) receiving HCQ 64 .…”
Section: The Anti-hyperlipidaemic Action Of Chloroquinementioning
confidence: 99%
“…En la búsqueda de interacciones entre ADO y DMARDs nos encontramos con un panorama diferente en el uso de hidroxicloroquina (HCQ) en artritis reumatoide, no necesariamente una (8) interacción . Se ha demostrado que casi el 50% de pacientes con artritis reumatoidea presentan (9) disminución de la sensibilidad a la insulina (SI) asociada a inflamación crónica . La hidroxicloroquina (HCQ) es un antimalárico, de buena tolerancia, se ha comprobado que además de su papel antiinflamatorio e inmunomodulador, la HCQ posee mecanismos directos sobre el metabolismo de la glucosa y de los lípidos, llevando a descenso en el colesterol total, los triglicéridos, elevación del HDL, que llevarían a los pacientes a un mejor control glucémico y a disminuir el riesgo de padecer diabetes (10) mellitus 2 .…”
Section: Antidiabéticos Orales Interacción Con Fármacos Modificadoresunclassified